¿Cabría un desmarketing a la concepción del marketing verde actual? Una crítica a la teoría y la práctica del marketing verde - Tola Cisneros, Myriam Tatiana (2014)
This article examines the concept of Green Marketing by reviewing literature on its theory and practice. First, the text presents a direct reflection on the most relevant contributions and implications in relation to Green Marketing and its possible need to refocus. Then, a general identification of the green consumer and their role in the environmental management process is given. Finally, this paper offers some considerations regarding the necessary application of the correct Sustainable Green Marketing concept within society. This review will help other researchers who seek to know the research status regarding Green Marketing. In addition, individuals and organizations will be able to benefit from the strategies of Green Marketing to develop sustainable socio- environmental marketing campaigns in order to generate a real change in human behavior towards the environment, with a perpetual and immutable consciousness that can be transmitted as an undeniable value from generation to generation.